PENGARUH IFRS TERHADAP PERWUJUDAN BISNIS YANG SEHAT DI INDONESIA - Setiajatnika, Eka; Sanubari, Sari; Inggit Yulinar, Ai; Nur Rahmawati, Astri (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2019)
This study aims to analyze the effect of accounting standards based on International Financial Reporting Standards (IFRS) on the realization of sound business in Indonesia by using benefits, the goals and advantages of IFRS itself, International Financial Reporting Standards (IFRS) are adopted standards, interpretations and frameworks. by an international accounting standards board (IASB) compiler body. Basically the business aims to seek profits or profits that are as large as possible, but a sound business requires more detailed and more open financial statements for both internal and external. The realization of a healthy business is projected with IFRS characters who are more transparent in making financial reports, strengthening informed economic accountability and contributing to economic efficiency by helping investors to identify a company and most importantly International Financial Reporting Standards (IFRS) is a global language where companies ( business) can be understood by the world market. Thus the business will progress significantly because it can enter the world capital market. The writing method used is a literature study where with this method we as authors seek information through books, journals, articles, thesis, laboratory manuals, theses, dissertations and other scientific works. All references are related to this paper and we have developed it so that there is a link between IFRS standards towards the realization of a healthy business in Indonesia. The results of our research prove that IFRS standards are capable of realizing a healthy and growing business globally. The conclusion of our research is that the benefits, objectives and characteristics of IFRS standards will be able to make businesses in Indonesia develop healthily and make the company easier to enter the world capitalmarket.